Estratégias de complexidade: práticas alternativas da habitação vertical coletiva paulistana (2007-2017) - Zillmer Neto , Ney Nicolau (2018)
The work has as central proposal the analysis of a set of multifamily housing buildings, built by private initiative in the city of São Paulo during the last decade (2007-2017), which presents as a common feature the ability to reconcile verticality and typological diversity: buildings in height, formed by the overlapping of various parts or housing typologies. Although the current context of Brazilian housing production demonstrates a certain tendency towards the standardization of architectural elements, such as the standard apartment or the pavementtype, research has raised examples that can be considered as "alternative practices" because of the diversity and complexity of solutions. In this sense, the work proposes a study of the different compositional mechanisms or "strategies of complexity" used by these buildings, with the aim of contributing to the study of the design discipline. To better elucidate and understand the spatial structures of the cases, the analysis adopts as a methodological tool the formal analytical method, supported by the conceptual diagrams and the axonometric perspective. The analysis structure proposed by the work has an increasing order and is divided into three formal moments or levels: Parts, Whole and Totality. The Parties correspond to the basic space structures or to the apartments and have three spatial categories: apartment-sandwich, apartment-mégaro and apartment-diagram. The Whole is dealing with the "complexity strategies" that structure the Parties and is organized through four verbal actions that have been identified by the work: Stacking, Interrupting, Assembling and Moving. Finally, the ultimate sphere or wholeness is responsible for addressing the relationship of the building to its surroundings. Among the projects identified as "alternative practices", the study selected three cases for a more in-depth reading, having as selection criteria the design complexity and scale difference: the 360 ° building tower and the Fidalga 772 and Camboriú building blocks.